From Cultural Tradition to Arts Industry: Development of The Ondel-Ondel as the Identity of the Betawi Community - Aryandari, Citra; Al Hazmi, Fariz; Oktaviela, Jibrilla (Harmonia: Journal of Arts Research and Education, 2026)
This study discusses changes and developments in the Ondel-ondel cultural identity within the Betawi Community. Ondel-ondel is the cultural identity of the Betawi people, which was previously used in their rituals and is now found only in several creative industries. The research method uses a qualitative, ethnographic approach across the stages of object selection, investigation, and interpretation. The research aims to discuss the changes and management of Ondel-ondel cultural identity, and to provide an overview of the development of Ondel-ondel as an identity. The main focus is on analyzing changes in the industrial realm and how society and the government manage them. Data collection was carried out through observation, interviews, and literature study. As the identity of the Betawi people and Jakarta, the development of Ondel-ondel is also influenced by several regional government policies. Now, Ondel-ondel is not only a cultural identity of the Betawi people but also an icon of the city of Jakarta. When the Betawi people no longer believe in rituals, they use and represent Ondel-ondel in other forms. Various forms of management are carried out on Ondel-ondel to make it a creative industry in society, including music, performing arts, craft products, and visual products. However, of course, problems and impacts occur through this management. This research is expected to provide an understanding of the management of Ondel-ondel culture, a form of the creative industry.